Study of CRFP Shell Structures under Dynamic Loading in Shock Tube Setup. (4th December 2014) - Khawaja, H. A.; Bertelsen, T. A.; Andreassen, R.; Moatamedi, M.
Abstract : The paper gives the study of the response of carbon fiber reinforced polymers (CRFP) quasi-isotropic shell structures under the influence of dynamic loading. The quasi-isotropic CRFP shell specimens are fabricated using Multipreg E720 laminates. These laminates are laid in such a way that shell structure has equal strength and mechanical properties in the two-dimensional (2D) plane and hence can be regarded as quasi-isotropic. In this study, the dynamic loading is generated using shock waves in a shock tube experimental setup. The strain and pressure data is collected from the experiments. Additional tests are carried out using Material Test System (MTS) for both tensile and flexural response of CRFP. Results obtained from experiments are compared with numerical simulations using ANSYS Multiphysics 14.0 finite element method (FEM) package. The numerical simulation and experimental results are found to be in good agreement.